IADC/SPE International Drilling Conference and Exhibition 2020
DOI: 10.2118/199654-ms
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Well Abandonments Using Shale as a Barrier

Abstract: Well abandonment is one of the biggest challenges in the oil and gas industry, both in terms of cost and effort as well as the technical hurdles associated with wellbore isolation for an indefinite term. A mechanism that may be exploited to simplify well abandonments is using natural shale formations for the creation of annular barriers. Currently, uncemented annuli often require casing milling and pulling before abandonment plugs can be set, which necessitates the use of a drilling rig. This is an expensive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It has been suggested that this phenomenon can potentially be useful in P&A [4,5]. Indeed, it has been confirmed in downscaled laboratory experiments that some shales like e.g., Lark-Horda can efficiently seal off annulus [6,7]. It has been shown that annulus closure may be induced by annulus pressure reduction and may be facilitated either thermally [8] or chemically [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that this phenomenon can potentially be useful in P&A [4,5]. Indeed, it has been confirmed in downscaled laboratory experiments that some shales like e.g., Lark-Horda can efficiently seal off annulus [6,7]. It has been shown that annulus closure may be induced by annulus pressure reduction and may be facilitated either thermally [8] or chemically [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been confirmed in downscaled laboratory experiments that some shales like e.g., Lark-Horda can efficiently seal off annulus [6,7]. It has been shown that annulus closure may be induced by annulus pressure reduction and may be facilitated either thermally [8] or chemically [6]. Bauer et al used controlled heating to stimulate plastic deformation in shale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations